1955
DOI: 10.1071/ch9550539
|View full text |Cite
|
Sign up to set email alerts
|

Studies in relation to biosynthesis. VII. 2-Hydroxy-6-methylbenzoic acid in Penicillium griseofulvum Dierckx

Abstract: The general problem of the biosynthesis of depsides and depsidones is considered. Feeding experiments using sodium acetate isotopically labelled in the carboxyl group have demonstrated that the mould Penicillium griseofulvum Dierckx (Raistrick's strain P68) elaborates 2-hydroxy-6-methylbenzoic acid (VII) by the head-to-tail linkage of acetic acid units in accord with the hypothesis of Birch and Donovan (1953). This demonstration constitutes the first definite support for the hypothesis based on bio- chemical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0
5

Year Published

1959
1959
2011
2011

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(63 citation statements)
references
References 0 publications
0
58
0
5
Order By: Relevance
“…3-Methylphenol (Tschinkel 1969;Attygalle et al 1991;Villaverde et al 2007;Geiselhardt et al 2009;), 3-ethylphenol (Tschinkel 1969;Geiselhardt et al 2009), 2-methylhydroquinone (Happ 1968;Wahrendorf and Wink 2006;Villaverde et al 2007;Geiselhardt et al 2009), and 2-ethylhydroquinone (Happ 1968;Hodges et al 1996;Wahrendorf and Wink 2006;Geiselhardt et al 2009) have all been detected in the defensive secretions of other tenebrionid beetles, although quinones are more ubiquitous 3-Methylphenol, 2-methylhydroquinone, and methyl-pbenzoquinone are thought to be sequential members of a biosynthetic pathway that originates with 6-methylsalicylic acid (Gnanasunderam et al 1984), itself formed from acetate (or malonate) units (Birch et al 1955). Similarly, 3-ethylphenol, 2-ethylhydroquinone, and ethyl-p-benzoquinone are likely derived from 6-ethylsalicylic acid (Gnanasunderam et al 1984), which differs in its synthesis by the use of a propionate unit in place of an acetate (or malonate) unit, as evidenced by isotope tracing experiments on ethyl-pbenzoquinone (Meinwald et al 1966).…”
Section: Discussionmentioning
confidence: 99%
“…3-Methylphenol (Tschinkel 1969;Attygalle et al 1991;Villaverde et al 2007;Geiselhardt et al 2009;), 3-ethylphenol (Tschinkel 1969;Geiselhardt et al 2009), 2-methylhydroquinone (Happ 1968;Wahrendorf and Wink 2006;Villaverde et al 2007;Geiselhardt et al 2009), and 2-ethylhydroquinone (Happ 1968;Hodges et al 1996;Wahrendorf and Wink 2006;Geiselhardt et al 2009) have all been detected in the defensive secretions of other tenebrionid beetles, although quinones are more ubiquitous 3-Methylphenol, 2-methylhydroquinone, and methyl-pbenzoquinone are thought to be sequential members of a biosynthetic pathway that originates with 6-methylsalicylic acid (Gnanasunderam et al 1984), itself formed from acetate (or malonate) units (Birch et al 1955). Similarly, 3-ethylphenol, 2-ethylhydroquinone, and ethyl-p-benzoquinone are likely derived from 6-ethylsalicylic acid (Gnanasunderam et al 1984), which differs in its synthesis by the use of a propionate unit in place of an acetate (or malonate) unit, as evidenced by isotope tracing experiments on ethyl-pbenzoquinone (Meinwald et al 1966).…”
Section: Discussionmentioning
confidence: 99%
“…[9] Little is known about the biosynthesis of these phytotoxic compounds (Scheme 1), except that they are derived from seven units of acetyl CoA like other salicylaldehyde-type congeners. [10,11] tatrienylsalicyl alcohol (7) is an important biosynthetic intermediate of salicylaldehyde-type polyketide synthesis, [8,12] because the fungus could oxidize (Z)-and (E)-1-phenylpropenes to racemic erythro-diol and optically active threo-diol, respectively. [13] We also assumed that heptatrienylsalicylaldehyde (8) could be an intermediate, because Iwasaki et al reported that aldehyde 2 was converted to alcohol 1 by the fungus.…”
Section: Introductionmentioning
confidence: 99%
“…Diese Erkenntnisse haben Birch zur Aufstellung der ,,Polyacetat-Regel" veranlal3t [I], die sich bei Strukturermittlungen auf dem Naturstoffgebiet als ungemein fruchtbar erwiesen hat und deren Giiltigkeit durch die klassischen Isotopenexperimente von Birch [2] und Ehrensviird [3] erstmals bewiesen wurde. Man nahm zunachst an, daJ3 die als Zwischenprodukte vermuteten Polyketomethylen-Strukturen durch Kondensation mehrerer Molekule Acetyl-CoA entstehen.…”
unclassified